PENGARUH CORPORATE GOVERNANCE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA PERUSAHAAN PUBLIK NON KEUANGAN - YUNIETHA YUNIETHA; AGUSTIN PALUPI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to analyze the effect of board of director, board of independence, audit quality, firm size, managerial ownership, profitability, leverage, sales growth and firm age toward earnings management. This study try to improve consistency of results from prior researchers. The sample of this study consist of 228 data from 76 non-financial sector companies that has been listing in Indonesia Stock Exchange for the period 2013 to 2015 by purposive sampling method. This study uses multiple regression method to investigate relation between each independent variable to earnings management. The research result shows that profitability and sales growth influence earnings management. On the other hand, board of director, board of independece, audit quality, firm size, managerial ownership, profitability, leverage, and firm age do not influence earnings management.